Agrarian Law and Enterprise Law (Revista da Faculdade de Direito, Universidade de São Paulo, 1999)
The main purpose of this paper is to distinguish Agrarian Law, on the one hand, from Civil Law and, on the other, from Commercial Law in a broad sense. In Private Law system, the distinction between act and activity allows one to separate Civil Law from Enterprise Law. Because it relates with some activities, not with some acts, Agrarian Law belongs to Enterprise Law and thus differs from Civil Law. Within the Enterprise Law limits one finds Commercial Law in a narrow sense and Industrial Law, which joined up form Commercial Law in a broad sense. Because it relates with some production activities, not with distribution activities of goods, Agrarian Law differs from Commercial Law in a narrow sense. To separate Agrarian Law from Industrial Law, however, another distinction (and a new one) is needed, i.e.: the function performed by the "ground", which is either the factor of production "land", in Agrarian Law; or just physical support that bears some parts of the factor of production "capital", in Industrial Law.